Expression of common fragile sites in two Ceboidea species: Saimiri boliviensis and Alouatta caraya (Primates: Platyrrhini) - Fundia, Ariela Freya (2000)
Fragile sites are points of preferential breakage that may be involved in chromosome rearrangements. Induction of common fragile sites (c-fra) and spontaneous breakage were analyzed in two New World Monkeys species: Saimiri boliviensis (SBO) and Alouatta caraya (ACA). Spontaneous chromosome aberrations were analyzed on untreated lymphocyte cultures with Brögger´s formula (1977). SBO presented a low level of spontaneous breakage, while higher frequencies were detected in ACA in which bands 1q23; 2q13 and 11q19 were significantly affected (p<0.01). The populational distribution of c-fra was analyzed by the Chi2 test in FUdR plus caffeine treated cultures. A total of 21 c-fra was identified in SBO and 24 in ACA. Fragile sites A1q33, B1p21, B4p14, C3q23 and C5q22 were identified in all analyzed SBO specimens. The most frequent c-fra identified in ACA specimens were 1q23, 1q31, 1q33, 2q22, 8q14, 12q31, 13q22, 14q15 and Xq22. Fragile sites A1q31, A1q33, B1q14, B3q13, B4q21 and Xq22 identified in SBO and 1q31, 1q33, 2q22, 4q21, 6q13, 13q22 and Xq22 from ACA were the most conserved sites. A low coincidence between the location of c-fra and that of heterochromatin and breakpoints involved in euchromatic rearrangements known for these genera, was established.